Clear coating composition and method for producing coated article
The clear coating composition, utilizing a combination of acrylic resins with different molecular weights and a slow-evaporating ketone solvent, addresses the need for high design and appearance properties and color reversion resistance, enhancing the performance and longevity of the coating film.
Patent Information
- Application Number
- CN202380017995.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-07-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-07-10
AI Technical Summary
Existing clear coating compositions do not adequately meet the demands for high design and appearance properties required by consumers, despite efforts to reduce volatile organic compound emissions, and suffer from insufficient color reversion resistance and appearance.
A clear coating composition comprising a combination of a primary hydroxyl-containing acrylic resin with a weight average molecular weight of 6,000 or less, a secondary hydroxyl-containing acrylic resin with a secondary hydroxyl-containing acrylic resin with a weight average molecular weight of 6,000 or more, a secondary hydroxyl-containing acrylic resin with a weight average molecular weight of 6,000 or more, and an organic solvent containing a ketone compound with 7 or more carbon atoms, at a solid content concentration of 55% by mass or more, which is maintained within a controlled viscosity range using a combination of resins with different reactivities and a slow-evaporating solvent.
The composition achieves a coating film with improved color reversion resistance, appearance, and workability, while maintaining a prolonged shelf life and controlled viscosity, ensuring high design and appearance properties.
Smart Images

Figure BDA0004953766540000191 
Figure BDA0004953766540000251 
Figure BDA0004953766540000261
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a clear coating composition and a coated article. Background Art
[0002] A clear coating film is generally formed as the outermost layer of a car body or the like, and the clear coating film is required to have high design properties and appearance.
[0003] In recent years, however, for environmental protection, it has been sought to reduce the emission of volatile organic compounds (VOC) from factories, etc. One method of reducing VOC emission is to increase the solid content concentration of the coating composition.
[0004] Patent Document 1 describes a coating composition comprising (A) a hydroxyl-containing acrylic resin having an acid value of 0 to 30 mgKOH / g, (B) a hydroxyl-containing acrylic resin having an acid value of 60 to 120 mgKOH / g, and (C) a polyisocyanate compound, wherein the solid content during coating is 50% by mass or more.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2022 / 107847 Summary of the invention
[0008] Problems to be solved by the invention
[0009] According to the clear coating composition described in Patent Document 1, a coating film having excellent color reversion resistance and appearance can be obtained. However, these properties are not yet sufficient at a time when consumers are increasingly demanding higher design and appearance due to their desire for higher quality.
[0010] An object of the present invention is to provide a clear coating composition capable of obtaining a coating film having excellent color reversion resistance and appearance, and a method for producing a coated article using the clear coating composition.
[0011] Means for solving problems
[0012] In order to solve the above-mentioned problems, the present invention provides the following aspects.
[0013] [1] A clear coating composition comprising a hydroxyl group-containing acrylic resin (A), a polyisocyanate compound (B) and an organic solvent (C),
[0014] The aforementioned hydroxyl-containing acrylic resin (A) comprises a primary hydroxyl-containing acrylic resin (A1) and a secondary hydroxyl-containing acrylic resin (A2).
[0015] The weight average molecular weight of the acrylic resin (A1) containing a primary hydroxyl group is 6,000 or less,
[0016] The weight average molecular weight of the acrylic resin (A2) containing a secondary hydroxyl group is 6,000 or more,
[0017] The organic solvent (C) contains a ketone compound (C1) having 7 or more carbon atoms,
[0018] The solid content concentration during coating is 55% by mass or more.
[0019] [2] The clear coating composition according to [1] above, wherein the acid value of the primary hydroxyl group-containing acrylic resin (A1) is 0 mgKOH / g or more and 40 mgKOH / g or less.
[0020] [3] The clear coating composition according to [1] or [2], wherein the acid value of the secondary hydroxyl group-containing acrylic resin (A2) is 0 mgKOH / g or more and 40 mgKOH / g or less.
[0021] [4] The clear coating composition according to any one of [1] to [3], wherein the weight average molecular weight of the primary hydroxyl group-containing acrylic resin (A1) is 3,000 or more and 6,000 or less.
[0022] [5] The clear coating composition according to any one of [1] to [4], wherein the mass ratio (A1) / (A2) of the content of the acrylic resin containing primary hydroxyl groups (A1) to the content of the acrylic resin containing secondary hydroxyl groups (A2) is 1 / 99 to 80 / 20.
[0023] [6] The clear coating composition according to any one of [1] to [5], wherein the clear coating composition has a solid content concentration of 60% by mass or more and 80% by mass or less 60 seconds after application during spray coating.
[0024] [7] The clear coating composition according to any one of [1] to [6], wherein the organic solvent (C) further contains at least one selected from the group consisting of monocarboxylic acid esters, dibasic ester compounds, cellosolves and carbitol having a boiling point of 200°C or higher.
[0025] [8] A method for producing a coated article, comprising:
[0026] A step of applying a base coating composition to an object to be coated to form an uncured base coating film;
[0027] A step of applying a clear coating composition to the uncured base coating film to form an uncured clear coating film; and
[0028] a step of simultaneously curing the uncured base coating film and the uncured clear coating film;
[0029] The clear coating composition comprises a hydroxyl-containing acrylic resin (A), a polyisocyanate compound (B) and an organic solvent (C).
[0030] The aforementioned hydroxyl-containing acrylic resin (A) comprises a primary hydroxyl-containing acrylic resin (A1) and a secondary hydroxyl-containing acrylic resin (A2).
[0031] The weight average molecular weight (Mw) of the acrylic resin (A1) containing a primary hydroxyl group is 6,000 or less,
[0032] The weight average molecular weight (Mw) of the acrylic resin (A2) containing a secondary hydroxyl group is 6,000 or more,
[0033] The organic solvent (C) contains a ketone compound (C1) having 7 or more carbon atoms,
[0034] The solid content concentration during coating is 55% by mass or more.
[0035] Effects of the Invention
[0036] According to the present invention, a clear coating composition capable of obtaining a coating film having excellent color reversion resistance and appearance can be provided. According to the present invention, a method for producing a coated article using the clear coating composition can also be provided. DETAILED DESCRIPTION
[0037] [Clear coating composition]
[0038] The transparent coating composition described in the present application comprises an acrylic resin (A) containing a hydroxyl group, a polyisocyanate compound (B) and an organic solvent (C). The acrylic resin (A) containing a hydroxyl group comprises an acrylic resin (A1) containing a primary hydroxyl group and an acrylic resin (A2) containing a secondary hydroxyl group. The weight average molecular weight (Mw) of the acrylic resin (A1) containing a primary hydroxyl group is 6,000 or less. The weight average molecular weight (Mw) of the acrylic resin (A2) containing a secondary hydroxyl group is 6,000 or more. The organic solvent (C) comprises a ketone compound (C1) having 7 or more carbon atoms. The solid content concentration of the transparent coating composition during coating is 55% by mass or more.
[0039] The clear coating composition is a two-component type consisting of a main agent comprising a hydroxyl-containing acrylic resin (A) and a solvent, and a curing agent comprising a polyisocyanate compound (B) and a solvent. At least a part of the solvent contained in the main agent and the curing agent is an organic solvent (C) containing a ketone compound (C1) having 7 or more carbon atoms.
[0040] The solid content concentration of the clear coating composition at the time of coating refers to the solid content concentration of the clear coating composition immediately after the main agent and the curing agent are mixed (within 10 minutes after mixing) and immediately before coating (within 10 minutes before coating). The solid content concentration of the clear coating composition at the time of coating is determined by measuring the mass of the residue (also referred to as the heating residue) after heating the clear coating composition within 10 minutes after the main agent and the curing agent are mixed at 140°C for 30 minutes.
[0041] Specifically, the solid content concentration C of the clear coating composition during coating is 1 The calculation can be performed as follows. First, determine the mass of an aluminum cup of appropriate size (initial mass W 0 Then, the clear coating composition is added to the aluminum cup within 10 minutes after the main agent and the curing agent are mixed, and the mass (W) is measured within 10 minutes after the addition. 1 ).
[0042] Next, the aluminum cup was heated at 140°C for 30 minutes and the mass (W 2 ). 2 is the total mass of the solid content (heating residue) of the clear coating composition and the aluminum cup. Finally, the solid content concentration C of the clear coating composition during coating is calculated using the following formula: 1 . (W 1 -W 0 ) represents the total mass of the solvent and solid content remaining in the clear coating composition immediately after coating. (W 2 -W 0 ) represents the mass of the solid content of the clear coating composition alone.
[0043] Solid content concentration C 1 (%) = 100 × (W 2 -W 0 ) / (W 1 -W 0 )
[0044] In a two-component coating composition, if the solid content concentration is high, the main agent and the curing agent are likely to react, and therefore, the shelf life is usually likely to be shortened. The shelf life refers to the time (usable time) during which the coating composition can be applied and can exert the expected coating performance, final appearance, design, etc. since the main agent and the curing agent are mixed. The viscosity of the coating composition beyond the shelf life is too high, and therefore, the performance and appearance of the coating obtained using it may be reduced. In order to extend the shelf life, it can be considered to control in a manner that no sharp reaction of the main agent and the curing agent occurs, or, even if a reaction is performed before coating, the viscosity can be maintained low.
[0045] In the present application, from the viewpoint of controlling the reaction, as the main agent, an acrylic resin (A1) containing a primary hydroxyl group and an acrylic resin (A2) containing a secondary hydroxyl group are used in combination. Generally, a primary hydroxyl group has a higher reactivity than a secondary hydroxyl group. By using acrylic resins containing hydroxyl groups with different reactivities in combination, the speed of the curing reaction can be controlled.
[0046] Furthermore, in order to maintain the viscosity low, a low molecular weight resin is used as the acrylic resin containing a highly reactive primary hydroxyl group. Thus, even if the acrylic resin (A1) containing a primary hydroxyl group and the polyisocyanate compound (B) react after the main agent and the curing agent are mixed, the viscosity increase of the entire clear coating composition can be suppressed.
[0047] That is, according to the present application, since the molecular weight of the acrylic resin (A1) containing a more reactive primary hydroxyl group is small, the reaction rate can be controlled and the viscosity increase of the clear coating composition can be suppressed. As a result, the shelf life is prolonged, and the coating performance and appearance of the obtained coating film are also improved. The appearance of the coating film can be evaluated by, for example, the smoothness and the presence or absence of oozing (small holes or protrusions on the surface of the coating film).
[0048] On the other hand, from the viewpoint of color reversion resistance, a high molecular weight resin is used as the acrylic resin (A2) containing a secondary hydroxyl group. Color reversion refers to a phenomenon in which the design property is reduced due to the penetration and mixing of the components of the clear coating composition into the coating film (e.g., a colored base coating film or a metal base coating film) in the lower layer. For example, in the case where the lower layer is a metal base coating film having a bright pigment, if the components of the clear coating composition penetrate into the lower layer, the arrangement of the bright pigment is disordered, and the desired FF property (flip flop property) cannot be obtained. This reduction in FF property is an example of color reversion. Color reversion resistance can be said to be a performance that the coating film in the lower layer of the clear coating film can exert a design property that will not be impaired by the clear coating composition. By using an acrylic resin (A2) containing a secondary hydroxyl group having a large molecular weight, the resin itself is not easy to penetrate into the lower layer, and other components with small molecular weight are inhibited from penetrating into the lower layer.
[0049] That is, according to the present application, since the molecular weight of the acrylic resin (A2) containing a secondary hydroxyl group having lower reactivity is large, the color reversion resistance can be improved.
[0050] However, in a two-component coating composition with a high solid content concentration, it is difficult to improve the appearance of the resulting coating film when only a low molecular weight acrylic resin (A1) containing primary hydroxyl groups and a high molecular weight acrylic resin (A2) containing secondary hydroxyl groups are used in combination. This is because if the solid content concentration is high, the viscosity during coating is also likely to become high. In the present application, a ketone compound (C1) having a carbon number of 7 or more is used in at least a portion of the organic solvent (C). Thus, the viscosity of the clear coating composition having a high solid content concentration during coating can be controlled to an appropriate range. As a result, the appearance of the resulting coating film becomes good. Moreover, workability is also improved. Although not bound by a specific theory, it can be considered that this is because: the evaporation rate of the ketone compound (C1) having a carbon number of 7 or more is slow (i.e., the boiling point is high to a certain extent), and the high molecular weight acrylic resin (A2) containing secondary hydroxyl groups can be well dispersed.
[0051] Solid content concentration C of the clear coating composition 1 It can be 56% by mass or more, 58% by mass or more, or 60% by mass or more. Even with such a high solid content concentration, the ketone compound (C1) having 7 or more carbon atoms can well disperse the high molecular weight acrylic resin (A2) containing secondary hydroxyl groups, so the viscosity of the clear coating composition during coating can be controlled to an appropriate range. Therefore, the appearance of the obtained coating film becomes good. The solid content concentration C of the clear coating composition 1 It may be 80% by mass or less, or 75% by mass or less.
[0052] The ketone compound (C1) having 7 or more carbon atoms can also easily increase the solid content concentration of the clear coating composition after 60 seconds of application (hereinafter referred to as coating solid content concentration C) during spray coating. 60 ) is controlled within an appropriate range. This is because the evaporation rate of the ketone compound (C1) having a carbon number of 7 or more is slow. The coating solid content concentration C of the clear coating composition described in the present application is 60 For example, it is 60% by mass or more and 80% by mass or less. By maintaining the solid content concentration not being too high for a predetermined time after the clear coating composition is applied, the self-leveling function of the coating composition is exerted, and the smoothness of the resulting coating film can be further improved. When the ketone compound (C1) having 7 or more carbon atoms is used and the solid content concentration during coating is set to 55% by mass or more, it is easy to increase the coating solid content concentration C1 to 50% by mass or more. 60 The content is adjusted to be 60% by mass or more and 80% by mass or less.
[0053] During coating, part of the solvent evaporates, so the solid content concentration of the coating after coating usually becomes higher. For previous coatings, in order to increase the solid content concentration during coating and reduce the viscosity during coating, solvents with small molecular weight such as butyl acetate are used. Solvents with small molecular weight are generally highly volatile, so the solid content concentration of the coating just after being applied to the coated object tends to become higher. Therefore, the self-leveling function cannot be exerted, and the smoothness of the resulting coating film is more likely to decrease. It can be considered that the ketone compound (C1) with a carbon number of 7 or more used in the clear coating composition described in the present application has a slow evaporation rate, so the coating solid content concentration C1 can be reduced. 60 Maintain within an appropriate range. Coating solid content concentration C 60 The coating solid content concentration C may be 65% or more, or 70% or more. 60 It may be 79% by mass or less, or 78% by mass or less.
[0054] Coating solid content concentration C of the clear coating composition 60 The calculation can be performed as follows. First, the mass (initial mass W) of a substrate (e.g., aluminum film) of appropriate size is measured. 0 ). Then, the substrate was spray-coated with a clear coating composition. 60 seconds after the spray coating was completed, the substrate was bent with the surface on which the clear coating composition was attached as the inner side in order to prevent the solvent from volatilizing. The mass (W) of the substrate with the uncured clear coating composition was measured. wet ). wet It is the total mass of the solvent and solid components remaining in the clear coating composition 60 seconds after spray coating, and the substrate.
[0055] Next, the substrate was opened and heated at 140° C. for 30 minutes to cure the clear coating composition. Thereafter, the mass (W) of the substrate having the cured clear coating composition was measured. dry ). dry It is the total mass of the solid content of the clear coating composition and the substrate.
[0056] Finally, the coating solid content concentration C was calculated using the following formula: 60 . (W wet -W 0 ) represents the total mass of the solvent and solid components remaining in the clear coating composition after spray coating for 60 seconds. (W dry -W 0 ) represents the mass of only the solid components of the clear coating composition.
[0057] Coating solid content concentration C 60 (%) = 100 × (W dry -W 0) / (W wet -W 0 )
[0058] (A) Hydroxyl-containing acrylic resin
[0059] The hydroxyl group-containing acrylic resin (A) includes a primary hydroxyl group-containing acrylic resin (A1) and a secondary hydroxyl group-containing acrylic resin (A2).
[0060] The acrylic resin (A1) containing a primary hydroxyl group (hereinafter also referred to as the first acrylic resin (A1)) contains a primary hydroxyl group but does not contain a secondary hydroxyl group. The acrylic resin (A2) containing a secondary hydroxyl group (hereinafter also referred to as the second acrylic resin (A2)) contains at least a secondary hydroxyl group and may further contain a primary hydroxyl group. The second acrylic resin (A2) may contain only a secondary hydroxyl group.
[0061] A primary hydroxyl group is a carbon atom that is bonded to only one carbon atom. α The bonded hydroxyl group is represented by "-CR 2 -C α H 2 -OH" represents an -OH group. A secondary hydroxyl group refers to a carbon atom C bonded to two carbon atoms. β The bonded hydroxyl group is represented by "-CR 2 -C β H(R 1 )-OH" represents an -OH group. R independently represents a hydrogen atom or a hydrocarbon group, R 1 It represents a hydrocarbon group.
[0062] The mass ratio (A1) / (A2) of the content of the first acrylic resin (A1) to the content of the second acrylic resin (A2) is, for example, 1 / 99 to 80 / 20. If the ratio of the first acrylic resin (A1) to the total mass of the first acrylic resin (A1) and the second acrylic resin (A2) is 1% by mass or more, the appearance of the resulting coating film can be further improved. If the ratio of the second acrylic resin (A2) to the total mass of the first acrylic resin (A1) and the second acrylic resin (A2) is 20% by mass or more, the color reversion resistance can be further improved.
[0063] If the mass ratio (A1) / (A2) is within the above range, it is easy to achieve both improvement in shelf life, coating film performance and appearance, and improvement in color reversion resistance. The mass ratio (A1) / (A2) may be 20 / 80 to 70 / 30, 30 / 70 to 60 / 40, or 30 / 70 to 50 / 50.
[0064] (A1) Acrylic resin containing primary hydroxyl groups
[0065] The weight average molecular weight (Mw) of the acrylic resin (first acrylic resin) (A1) containing a primary hydroxyl group is 6,000 or less. Thus, the viscosity of the clear coating composition during coating is maintained low. The Mw of the first acrylic resin (A1) may be 5,000 or less, 4,500 or less, or 4,000 or less.
[0066] The Mw of the first acrylic resin (A1) may be 1,000 or more, 2,000 or more, or 3,000 or more. This tends to increase the hardness of the resulting coating film. In one embodiment, the Mw of the first acrylic resin (A1) is 3,000 or more and 6,000 or less.
[0067] The Mw is determined by GPC using polystyrene as standard.
[0068] The acid value of the first acrylic resin (A1) is, for example, 0 mgKOH / g or more and 40 mgKOH / g or less. Thus, the shelf life can be sufficiently prolonged. The acid value of the first acrylic resin (A1) may be 1 mgKOH / g or more, and may be 3 mgKOH / g or more. The acid value of the first acrylic resin (A1) may be 30 mgKOH / g or less, 24 mgKOH / g or less, and 10 mgKOH / g or less.
[0069] The hydroxyl value of the first acrylic resin (A1) is, for example, 80 mgKOH / g or more and 250 mgKOH / g or less. Thus, sufficient crosslinking density can be obtained, and the hardness of the resulting coating film can be increased. The hydroxyl value of the first acrylic resin (A1) can be 100 mgKOH / g or more, and can be 120 mgKOH / g or more. The hydroxyl value of the first acrylic resin (A1) can be 220 mgKOH / g or less, and can be 200 mgKOH / g or less.
[0070] The hydroxyl value and the acid value are determined based on the solid content mass. The hydroxyl value and the acid value can be measured by a known method described in JIS K 0070: 1992. The hydroxyl value and the acid value can be calculated based on the amount of the unsaturated monomer in the raw material monomer of the resin (for example, the first acrylic resin (A1)).
[0071] The glass transition temperature (Tg) of the first acrylic resin (A1) is, for example, -20°C or higher and 60°C or lower. This can improve the durability of the obtained coating film, such as hardness and weather resistance. The Tg of the first acrylic resin (A1) may be 0°C or higher, or 5°C or higher. The Tg of the first acrylic resin (A1) may be 50°C or lower, or 40°C or lower.
[0072] Tg can be determined by calculation based on the type and amount of raw material monomers of the resin. Tg can be measured using a differential scanning calorimeter (DSC).
[0073] The first acrylic resin (A1) can be prepared by polymerizing an α,β-ethylenically unsaturated monomer having only a primary hydroxyl group and a third α,β-ethylenically unsaturated monomer having no primary or secondary hydroxyl group by a known method. The first acrylic resin (A1) is prepared, for example, by solution polymerization.
[0074] Examples of the α,β-ethylenically unsaturated monomer having only a primary hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-1-methyl (meth)acrylate, Placcell FM1 (ε-caprolactone-modified hydroxyethyl methacrylate, manufactured by Daicel Chemical Co., Ltd.), polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate. These may be used alone or in combination of two or more.
[0075] Examples of the third α,β-ethylenically unsaturated monomer include (meth)acrylate monomers such as methyl, ethyl, propyl, butyl, hexyl, ethylhexyl, lauryl, phenyl, isobornyl, and cyclohexyl (meth)acrylate; α,β-ethylenically unsaturated monomers containing an acid group such as acrylic acid, methacrylic acid, acrylic acid dimer, crotonic acid, 2-acryloyloxyethylphthalic acid, 2-acryloyloxyethylsuccinic acid, ω-carboxy-polycaprolactone mono(meth)acrylate, maleic acid, fumaric acid, and itaconic acid; vinyl alcohol ester monomers, which are esters of vinyl alcohol and carboxylic acids such as acetic acid and propionic acid; polymerizable unsaturated hydrocarbon monomers such as styrene, α-methylstyrene, vinylnaphthalene, butadiene, and isoprene; polymerizable nitrile monomers such as acrylonitrile and methacrylonitrile; and acrylamide monomers such as acrylamide, methacrylamide, N-hydroxymethylacrylamide, N,N-dimethylacrylamide, and diacetoneacrylamide. These monomers may be used alone or in combination of two or more.
[0076] (Meth)acrylate refers to acrylate and / or methacrylate.
[0077] (A2) Acrylic resin containing secondary hydroxyl groups
[0078] The weight average molecular weight (Mw) of the acrylic resin (second acrylic resin) (A2) containing a secondary hydroxyl group is 6,000 or more. This improves the color reversion resistance of the coating film. In addition, the coating film properties such as hardness, chemical resistance, scratch resistance and weather resistance can also be improved.
[0079] The Mw of the second acrylic resin (A2) may be 20,000 or less, or 12,000 or less. The Mw of the second acrylic resin (A2) may be 6,500 or more, or 7,000 or more.
[0080] The acid value of the second acrylic resin (A2) is, for example, 0 mgKOH / g or more and 50 mgKOH / g or less. The acid value of the second acrylic resin (A2) may be 1 mgKOH / g or more, 5 mgKOH / g or more, or 10 mgKOH / g or more. The acid value of the second acrylic resin (A2) may be 40 mgKOH / g or less, 35 mgKOH / g or less, or 30 mgKOH / g or less. In one embodiment, the acid value of the second acrylic resin (A2) is 0 mgKOH / g or more and 40 mgKOH / g or less.
[0081] The hydroxyl value of the second acrylic resin (A2) is, for example, 80 mgKOH / g or more and 250 mgKOH / g or less. Thus, sufficient crosslinking density can be obtained, and the hardness of the resulting coating film can be improved. The hydroxyl value of the second acrylic resin (A2) can be 100 mgKOH / g or more, and can be 120 mgKOH / g or more. The hydroxyl value of the second acrylic resin (A2) can be 220 mgKOH / g or less, and can be 200 mgKOH / g or less.
[0082] The acid value of the first acrylic resin (A1) and the second acrylic resin (A2) may both be 0 mgKOH / g or more and 40 mgKOH / g or less. The acid value of the second acrylic resin (A2) may be higher than that of the first acrylic resin (A1).
[0083] The glass transition temperature (Tg) of the second acrylic resin (A2) is, for example, -30°C or higher and 35°C or lower. This can improve the durability of the obtained coating film, such as hardness and weather resistance. The Tg of the second acrylic resin (A2) may be -15°C or higher, 0°C or higher, or 5°C or higher. The Tg of the second acrylic resin (A2) may be 30°C or lower, 25°C or lower, or 20°C or lower.
[0084] The second acrylic resin (A2) can be prepared by polymerizing an α,β-ethylenically unsaturated monomer having at least a secondary hydroxyl group and a fourth α,β-ethylenically unsaturated monomer having no secondary hydroxyl group by a known method. The second acrylic resin (A2) is prepared by, for example, solution polymerization.
[0085] Examples of the α,β-ethylenically unsaturated monomer having at least a secondary hydroxyl group include 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-hydroxybutyl (meth)acrylate, and these may be used alone or in combination of two or more.
[0086] Examples of the fourth α,β-ethylenically unsaturated monomer include the aforementioned α,β-ethylenically unsaturated monomer having only a primary hydroxyl group and the third α,β-ethylenically unsaturated monomer.
[0087] (Other hydroxyl-containing resins)
[0088] The clear coating composition may contain other hydroxyl-containing resins. Examples of other hydroxyl-containing resins include hydroxyl-containing polycarbonate resins, hydroxyl-containing urethane resins, hydroxyl-containing polyester resins, and hydroxyl-containing amino resins. These may be used alone or in combination of two or more.
[0089] The solid content of other hydroxyl-containing components in 100 parts by mass of the total solid content of the first and second hydroxyl-containing acrylic resins (A1, A2) and other hydroxyl-containing resins is, for example, 10 parts by mass or less, 5 parts by mass or less, or 3 parts by mass or less.
[0090] (Other resins)
[0091] The clear coating composition may contain other resins. Other resins include resins other than those mentioned above, such as polycarbonate resins, urethane resins, polyester resins, acrylic resins, amino resins, etc., which do not contain hydroxyl groups and do not fall within the above definition. They may be used alone or in combination of two or more.
[0092] (B) Polyisocyanate Compounds
[0093] The polyisocyanate compound (B) is a curing agent, and reacts with the hydroxyl group-containing resin to form a crosslinked structure, thereby curing the clear coating composition.
[0094] The polyisocyanate compound (B) has at least two isocyanate groups in one molecule. As the polyisocyanate compound, for example, aliphatic polyisocyanates, alicyclic polyisocyanates, aliphatic polyisocyanates having an aromatic ring not bonded to an isocyanate group in the molecule (aromatic aliphatic polyisocyanates), aromatic polyisocyanates, and derivatives of these polyisocyanates can be listed. Specifically, aromatic polyisocyanates such as toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, o-phthalylene diisocyanate, and m-phthalylene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate; polymers such as their biuret, urate, and adducts, etc. They are used alone or in combination of two or more.
[0095] The equivalent ratio (NCO / OH) of the isocyanate group contained in the polyisocyanate compound (B) to the hydroxyl group contained in the resin containing the hydroxyl group may be 0.7 or more, or 0.8 or more. The equivalent ratio (NCO / OH) may be 2.0 or less, or 1.8 or less, or 1.5 or less. In one embodiment, the equivalent ratio (NCO / OH) is 0.7 or more and 2.0 or less. If the equivalent ratio (NCO / OH) is within this range, a transparent coating film having excellent hardness and weather resistance is easily formed.
[0096] (Other curing agents)
[0097] The clear coating composition may include other curing agents except the polyisocyanate compound (B). As other curing agents, for example, amino resins, epoxy compounds, aziridine compounds, carbodiimide compounds and oxazoline compounds may be listed. They are used alone or in combination of two or more. The content of other curing agents is appropriately set according to the resin containing hydroxyl groups.
[0098] (C) Organic solvents
[0099] The organic solvent (C) contains a ketone compound (C1) having 7 or more carbon atoms (hereinafter sometimes referred to as a ketone compound (C1). Thus, the viscosity of the clear coating composition having a high solid content concentration during coating can be controlled to an appropriate range. On the other hand, the ketone compound (C1) has little effect on the properties of other components contained in the clear coating composition. Therefore, the properties of other components contained in the clear coating composition can be fully utilized to improve the physical properties of the resulting coating film.
[0100] The ketone compound has a -C(=O)- structure. Examples of the ketone compound (C1) include methyl amyl ketone (MAK), methyl isoamyl ketone (MIAK), 3-heptanone, 4-heptanone, 2-octanone, diisobutyl ketone, and isophorone. Among them, from the viewpoint of high solubility of the hydroxyl-containing acrylic resin (A), it is desirable that the ketone compound (C1) is linear. Examples of the linear ketone compound (C1) include MAK and 2-octanone.
[0101] From the viewpoint of solubility of the hydroxyl-containing acrylic resin (A), the number of carbon atoms of the ketone compound (C1) may be 9 or less. The number of carbon atoms of the ketone compound (C1) may be 7 or 8.
[0102] The organic solvent (C) may contain other organic solvents in addition to the ketone compound (C1). Examples of other organic solvents include ketone compounds having a carbon number of 6 or less, such as acetone, acetylacetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; aromatic hydrocarbons such as benzene, toluene, ethylbenzene, propylbenzene, tert-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, and decalin; monocarboxylic acid esters such as methyl acetate, ethyl acetate, n-butyl acetate, amyl acetate, and diethylene glycol monobutyl ether acetate (butyl carbitol acetate); dibasic ester compounds; methyl cellosolve, ethyl cellosolve, n-propyl cellosolve, isopropyl cellosolve, n-butyl cellosolve, isobutyl cellosolve, isopentyl cellosolve, phenyl cellosolve, Cellosolves such as benzyl cellosolve; carbitols such as methyl carbitol, ethyl carbitol, n-propyl carbitol, isopropyl carbitol, n-butyl carbitol, isobutyl carbitol, isoamyl carbitol, carbitol acetate, phenyl carbitol, benzyl carbitol; ethers such as ethylene glycol monoisopropyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol mono-n-butyl ether, ethylene glycol mono-tert-butyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol mono-n-butyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and dioxane; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, and isobutyl alcohol. These may be used alone or in combination of two or more.
[0103] However, an organic solvent having no hydroxyl group may be blended into the curing agent.
[0104] The organic solvent (C) may include a ketone compound (C1) and an organic solvent having a boiling point of 200°C or more. This can further improve the appearance of the resulting coating film. In particular, it may include at least one of monocarboxylic acid esters, dibasic ester compounds, cellosolves and carbitol having a boiling point of 200°C or more (hereinafter sometimes referred to as the second solvent (C2)). The second solvent (C2) may be used alone or in combination of two or more.
[0105] Dibasic ester compounds (also called dibasic acid esters) are obtained by the reaction of dicarboxylic acids and alcohols. Dibasic ester compounds are represented by the following general formula, for example:
[0106] R 3 OOC-R 2 -COOR 4
[0107] (Where R 2 , R 3 and R 4 Each is independently an aliphatic, alicyclic, aliphatic or aromatic hydrocarbon group having an aromatic ring.)
[0108] R 2 It can be an aliphatic hydrocarbon group. 2 In the formula (R), the carbon number of the aliphatic hydrocarbon group may be 1 to 6, 2 to 6, or 2 to 4. 2 In R 2 In the formula (R), the aliphatic hydrocarbon group may be straight chain or branched. 2 It may be a linear saturated aliphatic hydrocarbon group having 1 to 6 carbon atoms.
[0109] R 3 and R 4 It can be an aliphatic hydrocarbon group. 3 and R 4 In the formula (R), the carbon number of the aliphatic hydrocarbon group may be 1 to 6, 1 to 3, or 1 or 2. 3 and R 4 In R 3 and R 4 In the formula (R), the aliphatic hydrocarbon group may be straight chain or branched. 3 and R 4 It may be a linear saturated aliphatic hydrocarbon group having 1 to 6 carbon atoms. 3 and R 4 Can be the same or different. 3 and R 4 Can be the same.
[0110] Specific examples of suitable dibasic ester compounds include dimethyl succinate, diethyl succinate, di-n-propyl succinate, di-n-butyl succinate, di-n-pentyl succinate, di-n-hexyl succinate, dimethyl glutarate, diethyl glutarate, di-n-propyl glutarate, di-n-butyl glutarate, di-n-pentyl glutarate, di-n-hexyl glutarate, dimethyl adipate, diethyl adipate, di-n-propyl adipate, di-n-butyl adipate, di-n-hexyl adipate, Amyl ester, di-n-hexyl adipate, dimethyl pimelate, diethyl pimelate, di-n-propyl pimelate, di-n-butyl pimelate, di-n-pentyl pimelate, di-n-hexyl pimelate, dimethyl suberate, diethyl suberate, di-n-propyl suberate, di-n-butyl suberate, di-n-pentyl suberate, di-n-hexyl suberate, dimethyl azelaic acid, diethyl azelaic acid, di-n-propyl azelaic acid, di-n-butyl azelaic acid, di-n-pentyl azelaic acid, di-n-hexyl azelaic acid. They are used alone, or are used in combination of more than two kinds. For example, the alkyl esters of succinic acid, the alkyl esters of glutaric acid and the alkyl esters of adipic acid can be used in combination.
[0111] In the clear coating composition, the content of the second solvent (C2) is, for example, 20 parts by mass or more and 60 parts by mass or less relative to 100 parts by mass of the ketone compound (C1). The content of the second solvent (C2) may be 25 parts by mass or more, or 30 parts by mass or more. The content of the second solvent (C2) may be 55 parts by mass or less, or 50 parts by mass or less.
[0112] The organic solvent (C) may contain an organic solvent having a boiling point of less than 200°C (hereinafter referred to as the third solvent (C3)) in addition to the ketone compound (C1). Examples of the third solvent (C3) include organic solvents having a boiling point of less than 200°C among the substances exemplified above as other organic solvents. The content of the third solvent (C3) may be, for example, less than 20 parts by mass relative to 100 parts by mass of the content of the ketone compound (C1). The aforementioned content of the third solvent (C3) may be 10 parts by mass or less, 5 parts by mass or less, or 0 parts by mass.
[0113] (Other ingredients)
[0114] The clear coating composition may further contain a pigment and various additives. Examples of the additives include ultraviolet absorbers, antioxidants, defoamers, surface conditioners, and anti-pinhole agents.
[0115] [Painted items]
[0116] The clear coating composition described in the present application can be used to obtain a coated article. The coated article includes, for example, a coated article and a multilayer coating film including a base coating film and a clear coating film. The clear coating film is formed by the clear coating composition described in the present application. Thus, the coated article has excellent color fastness and appearance.
[0117] The base coating film is disposed between the object to be coated and the clear coating film. The multilayer coating film may further include a mid-coat coating film disposed between the object to be coated and the base coating film. That is, the coated article may include an object to be coated, and a multilayer coating film in which a mid-coat coating film, a base coating film, and a clear coating film are sequentially laminated.
[0118] (Object to be coated)
[0119] Examples of the material of the coating include metal, resin, and glass. Specifically, examples of the coating include automobile bodies and automobile body parts of cars, trucks, motorcycles, and buses, and automobile parts such as spoilers, bumpers, rearview mirror covers, body grills, and door handles.
[0120] Examples of the metal include iron, copper, aluminum, tin, zinc, and alloys thereof (e.g., steel). Examples of the metal to be coated include cold-rolled steel sheets, hot-rolled steel sheets, stainless steel, electrogalvanized steel sheets, hot-dip galvanized steel sheets, zinc-aluminum alloy plated steel sheets, zinc-iron alloy plated steel sheets, zinc-magnesium alloy plated steel sheets, zinc-aluminum-magnesium alloy plated steel sheets, aluminum plated steel sheets, aluminum-silicon alloy plated steel sheets, tin plated steel sheets, and the like.
[0121] The metal object to be coated may be subjected to surface treatment. Examples of the surface treatment include phosphate treatment, chromate treatment, zirconium chemical treatment, and composite oxide treatment. After the surface treatment, the metal object to be coated may be further coated with an electroplating paint. The electroplating paint may be cationic or anionic.
[0122] Examples of the resin include polypropylene resin, polycarbonate resin, urethane resin, polyester resin, polystyrene resin, ABS resin, vinyl chloride resin, and polyamide resin. The resin coating object may be subjected to a degreasing treatment.
[0123] (Middle coating film)
[0124] The mid-coat film is formed by a mid-coat coating composition. The mid-coat coating composition is described below. The film thickness (dry film thickness) of the mid-coat film after curing is, for example, 5 μm or more and 80 μm or less. The dry film thickness of the mid-coat film can be 10 μm or more. The dry film thickness of the mid-coat film can be 50 μm or less.
[0125] The thickness of the coating film can be measured using an electromagnetic film thickness meter (for example, SDM-miniR manufactured by SANKO Co., Ltd.). The thickness of the coating film is the average value of the coating film thickness at any five points.
[0126] (Base coating)
[0127] The base coating film is formed by a base coating composition. The base coating composition is described below. The base coating film can be a single layer or a laminated coating film of more than two layers. The dry film thickness of each layer in the base coating film is, for example, 5 μm or more and 35 μm or less. The dry film thickness of each layer in the base coating film can be 7 μm or more. The dry film thickness of each layer in the base coating film can be 30 μm or less.
[0128] (Transparent coating)
[0129] The transparent coating film is formed from the transparent coating composition described in the present application. The dry film thickness of the transparent coating film is, for example, 10 μm or more and 80 μm or less. The dry film thickness of the transparent coating film may be 20 μm or more. The dry film thickness of the transparent coating film may be 60 μm or less.
[0130] [Method for producing coated article]
[0131] The aforementioned coated article is manufactured by a method comprising, for example, the following steps: a step of applying a base coating composition on the coated object to form an uncured base coating film; a step of applying the clear coating composition described in the present application to the uncured base coating film to form an uncured clear coating film; and a step of simultaneously curing the uncured base coating film and the uncured clear coating film.
[0132] Before the step of applying the base coating composition, a step of applying the mid-coat coating composition to the object to be coated may be performed. When the base coating composition is applied, the mid-coat coating film may be cured or uncured. When the base coating composition is applied, the mid-coat coating film may be cured.
[0133] That is, the coated article can be manufactured by a method (two-coat one-bake method) having the following steps: a step of applying a mid-coat coating composition to the coated object and curing it to form a cured mid-coat coating film; a step of applying a base coating composition and a clear coating composition in sequence on the cured mid-coat coating film to form an uncured base coating film and a clear coating film in sequence; and a step of curing the uncured base coating film and the clear coating film together.
[0134] In addition, the coated article can be manufactured by a method (three-coat one-bake method) having the following steps: a step of sequentially coating a mid-coat coating composition, a base coating composition and a clear coating composition on the coated object to form an uncured mid-coat coating film, a base coating film and a clear coating film in sequence; and a step of curing the uncured mid-coat coating film, the base coating film and the clear coating film together.
[0135] Hereinafter, each step will be described by taking the case of manufacturing a coated article having a multilayer coating film in which a midcoat film, a base coating film, and a clear coating film are sequentially laminated by a two-coat one-bake method as an example. However, the method for manufacturing a coated article is not limited thereto.
[0136] (I) Step of forming a cured intermediate coating film
[0137] First, the midcoat coating composition is applied to the object to be coated to form an uncured midcoat film. The midcoat film improves the adhesion of the base film to the object to be coated. In addition, the coating surface is made uniform by the midcoat coating, and the unevenness of the base film is easily suppressed.
[0138] As the coating method, for example, a roller coater method, air jet coating, air jet coating, and rotary atomization coating can be listed. These methods can be combined with electrostatic coating. Among them, from the viewpoint of coating efficiency, rotary atomization electrostatic coating is preferably used. Rotary atomization electrostatic coating can use a rotary atomization electrostatic coating machine commonly known as "MICRO MICROBELL (μμBELL)", "MICROBELL (μBELL)", "METALLIC BELL (METABELL)", etc.
[0139] Next, the uncured mid-coat film is cured. The mid-coat coating composition can be cured by heating. The curing (heating) conditions are appropriately set according to the composition of the mid-coat coating composition, the material of the coated object, etc. The heating temperature is, for example, above 100°C and below 180°C, and can be above 120°C and below 160°C. The heating time can be appropriately set according to the heating temperature. When the heating temperature is above 100°C and below 180°C, the heating time is, for example, above 10 minutes and below 60 minutes, and can be above 10 minutes and below 30 minutes. The heating time refers to the time when the target temperature is reached in the heating device and the coated object maintains the target temperature, without considering the time until the target temperature is reached. As a heating device, a drying furnace using a heating source such as hot air, electricity, gas, infrared rays, etc. can be listed.
[0140] (Mid-coat coating composition)
[0141] The midcoat coating composition may be water-based or solvent-based. In a water-based coating composition, as a solvent, water is included in an amount of 50% by mass or more of the total solvent. In a solvent-based coating composition, as a solvent, an organic solvent is included in an amount of 50% by mass or more of the total solvent.
[0142] The midcoat coating composition may further include, for example, resins, pigments, and various additives on the basis of various solvents. Examples of the resin include acrylic resins, polyester resins, polyurethane resins, alkyd resins, fluororesins, epoxy resins, and polyether resins. One of these resins may be used alone, or two or more thereof may be used in combination. The midcoat coating composition may further include the above-mentioned curing agent.
[0143] (II) Step of forming an uncured base coating film
[0144] The base coating composition is applied on the cured mid-coat film to form an uncured base coating film. Two or more layers of uncured base coating films can be formed by applying the same or different base coating compositions more than twice. An interval of several minutes can be set between the application of the nth base coating composition and the application of the n+1th base coating composition.
[0145] As a coating method, the same method as the coating method of a mid-coat coating composition can be mentioned, for example.
[0146] After the base coating composition is applied and before the clear coating composition is applied, pre-drying (also referred to as preheating) can be performed. Thus, the dilution component contained in the base coating composition is suppressed from boiling in the curing process, and the generation of gushing out is easily suppressed. And then, the mutual mixing of the uncured base coating film and the clear coating composition is suppressed by pre-drying, and it is difficult to form a mixed layer. Therefore, the smoothness of the obtained coated article can be further improved.
[0147] Examples of the pre-drying method include a method of leaving the mixture at a temperature of 20°C to 25°C for 5 minutes to 15 minutes, and a method of heating the mixture at a temperature of 50°C to 80°C for 30 seconds to 10 minutes.
[0148] (Base coating composition)
[0149] The base coating composition can be water-based or solvent-based. The base coating composition can be water-based. The water-based base coating composition includes, for example, an acrylic resin emulsion, a water-soluble acrylic resin, a curing agent (typically, a melamine resin), and a polyether polyol resin. The base coating composition can also include a pigment and various additives.
[0150] (III) Step of forming an uncured clear coating film
[0151] The clear coating composition described in the present application is applied on an uncured base coating film to form an uncured clear coating film.
[0152] The coating method is not particularly limited. As the coating method, for example, the same method as the coating method of the midcoat coating composition can be cited. Among them, from the viewpoint of coating efficiency, rotary atomization electrostatic coating is preferred. After applying the clear coating composition, pre-drying can be performed in the same manner as described above.
[0153] (IV) Curing process
[0154] The uncured base coating film and the clear coating film are cured together. Each coating film can be cured by heating. The heating conditions can be the same as those of the intermediate coating film.
[0155] Example
[0156] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples.
[0157] First, a plurality of first acrylic resins (A1) and second acrylic resins (A2) were produced as described below. Table 1 shows the physical property values of the produced hydroxyl-containing acrylic resins.
[0158] The solid content concentration of the varnish obtained in Production Examples 1-1 to 1-3 and Production Examples 2-1 to 2-5 was determined by measuring the mass of the residue (heating residue) after heating at 150° C. for 60 minutes.
[0159] [Manufacturing Example 1-1] Manufacture of the First Acrylic Resin (A1-1)
[0160] 24.2 parts by mass of butyl acetate were added to an autoclave equipped with a stirrer, a temperature control device, a reflux condenser, a nitrogen inlet pipe and a liquid feeding pump, and the temperature was raised to 170° C. A monomer solution (a mixed solution containing 20 parts by mass of styrene, 13.2 parts by mass of 2-ethylhexyl acrylate, 26.4 parts by mass of 2-ethylhexyl methacrylate, 39.4 parts by mass of 2-hydroxyethyl methacrylate and 1.0 part by mass of methacrylic acid) and a mixed solution of 1.65 parts by mass of di-tert-amyl peroxide and 7.74 parts by mass of butyl acetate were added dropwise to the autoclave using a liquid feeding pump over 3 hours.
[0161] After the dropwise addition was completed, the temperature was maintained at 170° C. for 30 minutes and then cooled to 120° C. over 30 minutes. Then, a mixed solution of 0.2 parts by mass of di-tert-amyl peroxy-2-ethylhexanoate and 2.0 parts by mass of butyl acetate was added dropwise over 30 minutes using a liquid delivery pump.
[0162] Next, after the reaction was continued at 120° C. for 1 hour, 6.4 parts by mass of butyl acetate was added to obtain a varnish having a solid content concentration of 70.0% by mass and containing the first acrylic resin (A1-1) having an Mw of 4,000, a hydroxyl value of 170 mgKOH / g, an acid value of 7 mgKOH / g, and a Tg of 20° C.
[0163] [Manufacturing Example 1-2] Manufacture of the First Acrylic Resin (A1-2)
[0164] The same operation as in Production Example 1-1 was performed except that the amount of di-tert-amyl peroxide added dropwise together with the monomer solution was set to 1.08 parts by mass, thereby obtaining a varnish containing the first acrylic resin (A1-2) having an Mw of 6,000, a hydroxyl value of 170 mgKOH / g, an acid value of 7 mgKOH / g, and a Tg of 20° C. and having a solid content concentration of 70.1% by mass.
[0165] [Manufacturing Example 1-3] Manufacture of the First Acrylic Resin (A1-3)
[0166] A varnish containing a first acrylic resin (A1-3) having a Mw of 4,000, a hydroxyl value of 170 mgKOH / g, an acid value of 25 mgKOH / g, and a Tg of 20° C. and having a solid content concentration of 70.0% was obtained in the same manner as in Production Example 1-1 except that the amount of 2-ethylhexyl acrylate in the monomer solution was 17.4 parts by mass, the amount of 2-ethylhexyl methacrylate was 19.4 parts by mass, and the amount of methacrylic acid was 3.8 parts by mass.
[0167] [Manufacturing Example 2-1] Manufacture of Second Acrylic Resin (A2-1)
[0168] 38.2 parts by mass of butyl acetate were added to a container equipped with a stirrer, a temperature control device, a reflux condenser and a dropping funnel, and the temperature was raised to 120° C. A monomer solution (a mixed solution comprising 20 parts by mass of styrene, 15.8 parts by mass of n-butyl acrylate, 21.8 parts by mass of n-butyl methacrylate, 41.1 parts by mass of 2-hydroxypropyl methacrylate and 1.3 parts by mass of acrylic acid) and a mixed solution of 11.0 parts by mass of tert-butyl peroxy-2-ethylhexanoate and 5 parts by mass of butyl acetate were simultaneously added dropwise to the container over 3 hours.
[0169] After leaving it for 30 minutes, a mixed solution of 0.5 parts by mass of tert-butyl peroxy-2-ethylhexanoate and 4 parts by mass of butyl acetate was added dropwise over 30 minutes. Then, the reaction was continued at 120° C. for 1 hour, and then 7 parts by mass of butyl acetate was added. Thus, a varnish having a solid content concentration of 64.5% was obtained, which contained a second acrylic resin (A2-1) containing a secondary hydroxyl group having an Mw of 8,000, a hydroxyl value of 160 mgKOH / g, an acid value of 10 mgKOH / g, and a Tg of 20° C.
[0170] [Manufacturing Example 2-2] Manufacture of Second Acrylic Resin (A2-2)
[0171] The same procedures as in Production Example 2-1 were performed except that the amount of tert-butyl peroxy-2-ethylhexanoate added dropwise together with the monomer solution was 4.5 parts by mass, thereby obtaining a varnish having a solid content concentration of 64.8% by mass, comprising a second acrylic resin (A2-2) containing a secondary hydroxyl group having an Mw of 12,000, a hydroxyl value of 160 mgKOH / g, an acid value of 10 mgKOH / g, and a Tg of 20°C.
[0172] [Manufacturing Example 2-3] Manufacture of Second Acrylic Resin (A2-3)
[0173] A varnish having a solid content concentration of 64.2% was obtained by the same procedure as in Production Example 2-1, except that the amount of n-butyl acrylate in the monomer solution was 18.3 parts by mass, the amount of n-butyl methacrylate was 14.8 parts by mass, and the amount of acrylic acid was 5.8 parts by mass. The varnish contained a second acrylic resin (A2-3) containing a secondary hydroxyl group having an Mw of 8,000, a hydroxyl value of 160 mgKOH / g, an acid value of 45 mgKOH / g, and a Tg of 20°C.
[0174] [Manufacturing Example 2-4] Manufacture of Second Acrylic Resin (A2-4)
[0175] The same procedures as in Production Example 2-1 were carried out except that the amount of n-butyl acrylate in the monomer solution was 1.4 parts by mass, the amount of n-butyl methacrylate was 36.2 parts by mass, and the amount of tert-butyl peroxy-2-ethylhexanoate added dropwise together with the monomer solution was 3.0 parts by mass, thereby obtaining a varnish having a solid content concentration of 65.1% by mass, which contained a second acrylic resin (A2-4) containing a secondary hydroxyl group and having an Mw of 15,000, a hydroxyl value of 160 mgKOH / g, an acid value of 10 mgKOH / g, and a Tg of 35°C.
[0176] [Manufacturing Example 2-5] Manufacture of Second Acrylic Resin (A2-5)
[0177] A varnish having a solid content concentration of 64.7% was obtained by the same procedure as in Production Example 1-1, except that 39.4 parts by mass of 2-hydroxyethyl methacrylate in the monomer solution was replaced with 39.4 parts by mass of 2-hydroxypropyl methacrylate. The varnish contained a second acrylic resin (A2-5) having a Mw of 4,000, a hydroxyl value of 150 mgKOH / g, an acid value of 7 mgKOH / g, and a Tg of 10°C and having a secondary hydroxyl group.
[0178] [Table 1]
[0179]
[0180] [Example 1]
[0181] (1) Preparation of main agent
[0182] In a 1L metal container, 42 parts by mass of the first acrylic resin (A1-1), 18 parts by mass of the second acrylic resin (A2-1), 2.0 parts by mass of an ultraviolet absorber, 1.0 parts by mass of a light stabilizer, 1.0 parts by mass of a surface conditioner, 18 parts by mass of a ketone compound (C1-1), and 13 parts by mass of a second solvent (C2) were added in order, and the mixture was stirred sufficiently with a disperser to obtain a main agent. The mass of the compounded parts is the solid content.
[0183] (2) Preparation of curing agent
[0184] In another metal container, 40 parts by mass of the polyisocyanate compound (B-1) and 12.0 parts by mass of the ketone compound (C1-1) were added in this order and stirred to obtain a curing agent.
[0185] (3) Preparation of clear coating composition
[0186] The main agent and the curing agent are mixed to obtain a clear coating composition.
[0187] [Examples 2 to 17 and Comparative Examples 1 to 6]
[0188] Clear coating compositions were prepared by the same procedures as in Example 1 except that the types and amounts of the blended components, the solid content during coating, and the like were changed as shown in Tables 2 to 4.
[0189] The details of each component shown in Tables 2 to 4 are as follows.
[0190] (Polyisocyanate compound (B))
[0191] (B-1): SUMIDUL N-3300 (manufactured by Sumika Combustion Laboratories, isocyanurate of hexamethylene diisocyanate, solid content concentration: 100% by mass)
[0192] (B-2): Desmogel N-3600 (manufactured by Sumika Combustrol Reitan Co., Ltd., isocyanurate of hexamethylene diisocyanate, solid content concentration: 100% by mass)
[0193] (B-3): Duranet TKA-100 (manufactured by Asahi Kasei Corporation, isocyanurate of hexamethylene diisocyanate, solid content concentration: 100% by mass)
[0194] (B-4): Dulanet TPA-100 (manufactured by Asahi Kasei Corporation, isocyanurate of hexamethylene diisocyanate, solid content concentration: 100% by mass)
[0195] (Ketone compound (C1))
[0196] (C1-1): Methyl amyl ketone
[0197] (C1-2): Methyl isoamyl ketone
[0198] (C1-3): 2-Octanone
[0199] (Second solvent)
[0200] (C2): DBE dibasic ester (manufactured by Shoei Chemical Co., Ltd., a mixture of dimethyl succinate, dimethyl glutarate and dimethyl adipate, CAS No. 95481-62-2), boiling point: 200°C
[0201] (Third solvent)
[0202] (C3-1): Butyl acetate, boiling point: 126°C
[0203] (C3-2): Methyl ethyl ketone, boiling point: 79.5°C
[0204] (C3-3): Methyl isobutyl ketone, boiling point: 116.2°C
[0205] (other)
[0206] UV absorber: Thunbine 384, manufactured by BASF
[0207] Light stabilizer: Thunbine 123, manufactured by BASF
[0208] Surface conditioner: BYK-350, manufactured by ビックケミー・ジャパン Co., Ltd.
[0209] [evaluate]
[0210] The following evaluations were performed using the clear coating compositions prepared in the above Examples and Comparative Examples. The evaluation results are shown in Tables 2 to 4.
[0211] (1) Validity period
[0212] The main agent and curing agent prepared above were mixed for 1 minute using a disperser, and the resulting mixture was temperature-adjusted to 20°C. Within 5 minutes after the start of mixing the main agent and curing agent, the initial viscosity V at 20°C was measured using a Ford cup No. 4. 0 Next, the mixture was left to stand for 1 hour under standard conditions (23°C, humidity 68%). Thereafter, the mixture was adjusted to 20°C and the viscosity V at 20°C was measured using Ford Cup No. 4. 1 .
[0213] The thickening ratio was calculated using the following formula and evaluated according to the following criteria: The lower the thickening ratio, the longer the shelf life.
[0214] Thickening ratio (%) = 100 × (V 1 -V 0 ) / V 0
[0215] (Evaluation Criteria)
[0216] A: Thickening ratio is less than 25%
[0217] B: Thickening ratio is 25% or more and less than 40%
[0218] C: Thickening ratio is more than 40%
[0219] (2) Solid content concentration C during coating 1
[0220] Measure the initial mass (W) of an aluminum cup with a diameter of about 6 cm 0 A clear coating composition obtained by mixing a main agent and a curing agent is added thereto, and its mass (W) is measured within 10 minutes after mixing. 1 The sample was heated in a spray oven at 140°C for 30 minutes and then cooled naturally, and the mass (W 2 Finally, the solid content concentration C during coating was calculated using the following formula: 1 .
[0221] Solid content concentration during coating C 1 (mass %) = 100 × (W 2 -W 0 ) / (W 1 -W 0 )
[0222] (3) Coating solid content concentration C 60
[0223] The initial mass (W) of an aluminum film of 14 cm in length × 9 cm in width × 15 μm in thickness was measured. Next, the aluminum film was attached to a tin-plated plate of 20 cm in length × 15 cm in width using a peeling tape so that the evaluation area reached 55 cm 2 (10 cm long × 5.5 cm wide) to make an evaluation sample. The clear coating composition is air-sprayed on the evaluation sample using the following spraying conditions. After air spraying, the aluminum film is immediately peeled off from the tinplate and the air-sprayed surface is bent inside. The mass (Wwet) of the bent aluminum film is measured. Next, the aluminum film is opened and sintered at 140°C for 30 minutes in a spray oven. After the evaluation sample is left to cool to room temperature, the mass (Wdry) of the aluminum film is measured. Finally, the coating solid content concentration C is calculated using the following formula: 60 .
[0224] Coating solid content concentration C 60 (mass %) = 100 × (W dry -W) / (W wet -W)
[0225] (Air injection conditions)
[0226] Spray volume: 220cc / min
[0227] Air motor: 30,000rpm
[0228] Voltage: -90kV
[0229] Line speed: 400mm / sec
[0230] Hole distance: 125mm
[0231] Gun distance: 250mm
[0232] Spray chamber conditions: 24°C, humidity 68%
[0233] (4) Film smoothness
[0234] (a) Preparation of Test Plate A
[0235] A zinc phosphate treated matte steel plate having a thickness of 0.8 mm, a length of 30 cm, and a width of 40 cm was electroplated with a cationic electroplating paint "Pavotop U-50" (manufactured by Nippon Payton Automode Coatings Co., Ltd.) in such a way that the dry film thickness became 20 μm, and baked at 160° C. for 30 minutes.
[0236] On the obtained coated plate, a gray mid-coat "Oluga OP-30" (a polyester-melamine paint manufactured by Nippon Paint Automotive Coatings Co., Ltd.) diluted to a viscosity of 25 seconds (measured at 20°C using a No. 4 Ford cup) was applied in two stages by air spraying so that the dry film thickness became 35 μm, and the coating was baked at 140°C for 30 minutes.
[0237] On the obtained coated plate, a water-based base coating was applied in two stages using a cartridge bell at a room temperature of 23°C and a humidity of 68% so that the dry film thickness was 15 μm. An interval of 1 minute and 30 seconds was set between the first and second coatings. After the second coating, a setting of 1 minute and 30 seconds was performed. Then, preheating was performed at 80°C for 5 minutes to form an uncured first base coating film.
[0238] As the aforementioned water-based base paint, a water-based paint produced by Nippon Paint Automotive Coatings Co., Ltd., which has a trade name of "Acarex AR-3000 (black)" and contains a black pigment as a coloring pigment, was used, which was diluted with deionized water to a viscosity of 6,000 mPa·s (measured using a B-type viscometer at 6 rpm and 20° C.).
[0239] On the obtained uncured first base coating film, a water-based metallic base coating was applied in two stages using a cartridge rotary cup. An interval of 1 minute and 30 seconds was set between the first and second coatings. After the second coating, a conditioning was performed for 1 minute and 30 seconds. Then, preheating was performed at 80°C for 5 minutes to form an uncured second base coating film.
[0240] As the water-based metallic base paint, a water-based paint composition containing an aluminum pigment and marketed under the trade name of "Aquarex AR-3000 (metal)" manufactured by Nippon Paint Automotive Coatings Co., Ltd. was used.
[0241] Next, the clear coating composition was applied in one step to the obtained coated plate so that the dry film thickness was 35 μm, and the coating was adjusted for 7 minutes. Next, the plate was baked in a dryer at 140° C. for 30 minutes to obtain a test plate A having a multilayer coating film.
[0242] (b) Determination and evaluation of LW value
[0243] The Long Wave (LW) value of the test plate A was measured using a "wave scanner DOI" (manufactured by BYK Gardner) (measurement wavelength: 1,300 to 12,000 μm), and the smoothness of the resulting coating film was evaluated according to the following criteria. The smaller the LW value, the higher the smoothness of the coating film.
[0244] (Evaluation Criteria)
[0245] A: LW value is less than 10
[0246] B: LW value is more than 10 and less than 15
[0247] C: LW value exceeds 15
[0248] (5) Anti-gushing
[0249] (a) Preparation of test plate B
[0250] Two 10-hole empty zinc phosphate treated plates (100 mm x 500 mm) were connected and coated with a clear coating composition by air jet coating under the following conditions to change the film thickness. Then, after conditioning for 7 minutes, the plates were baked in a dryer at 140°C for 30 minutes to obtain a test plate B.
[0251] (Air spray coating conditions)
[0252] Spray volume: 280cc / min
[0253] Air motor: 30,000rpm
[0254] Voltage: -90kV
[0255] Line speed: varies with film thickness from 20μm to 70μm
[0256] Hole distance: 125mm
[0257] Gun distance: 250mm
[0258] Spray chamber conditions: 24°C, humidity 68%
[0259] (b) Determination and evaluation of the burst limit film thickness
[0260] The obtained test plate B was visually observed to determine the film thickness at which the gushing out occurred, and the evaluation was performed according to the following criteria: The larger the film thickness at which the gushing out occurred, the better the gushing out resistance.
[0261] (Evaluation Criteria)
[0262] A: No oozing out even when the film thickness is 60 μm or more
[0263] B: The film thickness is 40 μm or more and less than 60 μm, and oozing occurs
[0264] C: Film thickness is less than 40μm, and gushing occurs
[0265] (6) Color fastness
[0266] The L values of the test plate A prepared in the same manner as above were measured at an incident angle of 45 degrees and a light receiving angle of 15 degrees using a multi-angle spectrophotometer "MA-68II" (trade name, manufactured by X-Rite Corporation). * Value (L * 15 value) and the light receiving angle is 110 degrees L * Value (L * 110 value), find the FF value (=L * 15 Value / L * 110 The calculated FF value was used to evaluate the color fastness according to the following criteria. The larger the FF value, the better the color fastness.
[0267] (Evaluation Criteria)
[0268] A: FF value is 5.5 or above
[0269] B: FF value is 5.0 or more and less than 5.5
[0270] C: FF value is less than 5.0
[0271] [Table 2]
[0272]
[0273] [Table 3]
[0274]
[0275] [Table 4]
[0276]
[0277] Examples 1 to 16 are examples of the present invention, and coating films excellent in color reversion resistance and appearance (coating film smoothness and oozing resistance) can be obtained.
[0278] Comparative Examples 1 to 3 are examples in which the ketone compound (C1) having 7 or more carbon atoms was not contained, and the appearance of the obtained coating films (coating film smoothness and anti-swelling properties) was not sufficiently satisfactory.
[0279] Comparative Example 4 is an example in which the acrylic resin (A2) containing a secondary hydroxyl group is not contained, and the obtained coating film did not have sufficiently satisfactory color reversion resistance.
[0280] Comparative Example 5 is an example in which the primary hydroxyl group-containing acrylic resin (A1) is not contained, and the pot life of the obtained coating composition and the appearance of the obtained coating film (coating film smoothness, anti-pouring property) were not sufficiently satisfactory.
[0281] Comparative Example 6 is an example in which a resin having a weight average molecular weight of less than 6,000 was used as the acrylic resin (A2) containing a secondary hydroxyl group, and the obtained coating film did not have sufficient reversion resistance.
[0282] This application includes the following aspects.
[0283] [1] A clear coating composition comprising a hydroxyl group-containing acrylic resin (A), a polyisocyanate compound (B) and an organic solvent (C),
[0284] The aforementioned hydroxyl-containing acrylic resin (A) comprises a primary hydroxyl-containing acrylic resin (A1) and a secondary hydroxyl-containing acrylic resin (A2).
[0285] The weight average molecular weight of the acrylic resin (A1) containing a primary hydroxyl group is 6,000 or less,
[0286] The weight average molecular weight of the acrylic resin (A2) containing a secondary hydroxyl group is 6,000 or more,
[0287] The organic solvent (C) contains a ketone compound (C1) having 7 or more carbon atoms,
[0288] The solid content concentration during coating is 55% by mass or more.
[0289] [2] The clear coating composition according to [1] above, wherein the acid value of the primary hydroxyl group-containing acrylic resin (A1) is 0 mgKOH / g or more and 40 mgKOH / g or less.
[0290] [3] The clear coating composition according to [1] or [2], wherein the acid value of the secondary hydroxyl group-containing acrylic resin (A2) is 0 mgKOH / g or more and 40 mgKOH / g or less.
[0291] [4] The clear coating composition according to any one of [1] to [3], wherein the weight average molecular weight of the primary hydroxyl group-containing acrylic resin (A1) is 3,000 or more and 6,000 or less.
[0292] [5] The clear coating composition according to any one of [1] to [4], wherein the mass ratio (A1) / (A2) of the content of the acrylic resin containing primary hydroxyl groups (A1) to the content of the acrylic resin containing secondary hydroxyl groups (A2) is 1 / 99 to 80 / 20.
[0293] [6] The clear coating composition according to any one of [1] to [5], wherein the clear coating composition has a solid content concentration of 60% by mass or more and 80% by mass or less 60 seconds after application during spray coating.
[0294] [7] The clear coating composition according to any one of [1] to [6], wherein the organic solvent (C) further contains at least one selected from the group consisting of monocarboxylic acid esters, dibasic ester compounds, cellosolves and carbitol having a boiling point of 200°C or higher.
[0295] [8] A method for producing a coated article, comprising:
[0296] A step of applying a base coating composition to an object to be coated to form an uncured base coating film;
[0297] A step of applying a clear coating composition to the uncured base coating film to form an uncured clear coating film; and
[0298] a step of simultaneously curing the uncured base coating film and the uncured clear coating film;
[0299] The clear coating composition comprises a hydroxyl-containing acrylic resin (A), a polyisocyanate compound (B) and an organic solvent (C).
[0300] The aforementioned hydroxyl-containing acrylic resin (A) comprises a primary hydroxyl-containing acrylic resin (A1) and a secondary hydroxyl-containing acrylic resin (A2).
[0301] The weight average molecular weight (Mw) of the acrylic resin (A1) containing a primary hydroxyl group is 6,000 or less,
[0302] The weight average molecular weight (Mw) of the acrylic resin (A2) containing a secondary hydroxyl group is 6,000 or more,
[0303] The organic solvent (C) contains a ketone compound (C1) having 7 or more carbon atoms,
[0304] The solid content concentration during coating is 55% by mass or more.
[0305] Industrial Applicability
[0306] The clear coating composition of the present invention can obtain a coating film having excellent color reversion resistance and appearance, and is therefore suitable for forming various clear coating films, especially clear coating films for automobiles.
[0307] This application claims priority based on Japanese Patent Application No. 2022-206526 filed in Japan on December 23, 2022, the entire contents of which are incorporated herein by reference.
Claims
1. A clear coating composition comprising a hydroxyl-containing acrylic resin (A), a polyisocyanate compound (B) and an organic solvent (C), The aforementioned hydroxyl-containing acrylic resin (A) comprises a primary hydroxyl-containing acrylic resin (A1) and a secondary hydroxyl-containing acrylic resin (A2). The weight average molecular weight of the acrylic resin (A1) containing a primary hydroxyl group is 6,000 or less, The weight average molecular weight of the acrylic resin (A2) containing a secondary hydroxyl group is 6,000 or more, The organic solvent (C) contains a ketone compound (C1) having 7 or more carbon atoms, The solid content concentration during coating is 55% by mass or more.
2. The clear coating composition according to claim 1, wherein The acid value of the primary hydroxyl group-containing acrylic resin (A1) is 0 mgKOH / g or more and 40 mgKOH / g or less.
3. The clear coating composition according to claim 1 or 2, wherein: The acid value of the secondary hydroxyl group-containing acrylic resin (A2) is 0 mgKOH / g or more and 40 mgKOH / g or less.
4. The clear coating composition according to any one of claims 1 to 3, wherein The weight average molecular weight of the primary hydroxyl group-containing acrylic resin (A1) is 3,000 or more and 6,000 or less.
5. The clear coating composition according to any one of claims 1 to 4, wherein The mass ratio (A1) / (A2) of the content of the acrylic resin (A1) containing a primary hydroxyl group to the content of the acrylic resin (A2) containing a secondary hydroxyl group is 1 / 99 to 80 / 20.
6. The clear coating composition according to any one of claims 1 to 5, wherein The clear coating composition has a solid content concentration of 60% by mass or more and 80% by mass or less 60 seconds after application in the case of spray coating.
7. The clear coating composition according to any one of claims 1 to 6, wherein The organic solvent (C) further contains at least one selected from the group consisting of monocarboxylic acid esters, dibasic ester compounds, cellosolves, and carbitol having a boiling point of 200° C. or higher.
8. A method for producing a coated article, comprising: A step of applying a base coating composition to an object to be coated to form an uncured base coating film; A step of applying a clear coating composition to the uncured base coating film to form an uncured clear coating film; and a step of simultaneously curing the uncured base coating film and the uncured clear coating film; The clear coating composition comprises a hydroxyl-containing acrylic resin (A), a polyisocyanate compound (B) and an organic solvent (C). The aforementioned hydroxyl-containing acrylic resin (A) comprises a primary hydroxyl-containing acrylic resin (A1) and a secondary hydroxyl-containing acrylic resin (A2). The weight average molecular weight (Mw) of the acrylic resin (A1) containing a primary hydroxyl group is 6,000 or less, The weight average molecular weight (Mw) of the acrylic resin (A2) containing a secondary hydroxyl group is 6,000 or more, The organic solvent (C) contains a ketone compound (C1) having 7 or more carbon atoms, The solid content concentration during coating is 55% by mass or more.
Citation Information
Patent Citations
Aqueous two-package type clear coating composition and process for the formation of multilayer finish coating film
CN101528872A
Coating composition and coating object
CN104673073A
High-solid coating composition
CN107177294A
Aqueous coating material for floor and floor coating method
JP2007126623A
Method for forming laminated coating film, and coated article
JP2010253383A
